Consideration given to usefulness of the concept of a medical error to determine criminal responsibility of a phisician for effects created in treatment process and adverse to a patient’s life and health - Dąbek, Aleksandra (Acta Universitatis Lodziensis. Folia Iuridica, 2016)
The purpose of the article is to present evolution of a medical error definition, including various opinions and interpretation doubts which appear around this issue as well as to judge whether the term is useful for determining criminal responsibility of a physician for causing negative effects to a patient’s life and health as a result of treatment procedure. The consideration concentrates on two areas, namely presenting views on the medical error from literature and jurisdiction as well as locating the concept of the medical error in the structure of a substantive offence committed unintentionally. The assessment particularly concerns the relationship between the medical error and the violation of rules of appropriate conduct with legal good against an offence committed unintentionally called violation of prudence rules required under some circumstances. At the end of the paper there are presented arguments against recognizing the medical error as a separate factor of criminal responsibility for perpetration of a substantive offence committed unintentionally in the process of providing health services as well as reasons for replacing the term “medical error” by a concept of a wider category, namely “violation of rules of prudence required under some circumstances”.